Student Creativity Education in Plastic Waste Processing Innovation - Setiawan, Tulus; Suwanda, Rizki; Anshari, Said Fadlan; Husna, Nur Fazri; Sartika, Tiara (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to address environmental problems, emphasizing project-based learning, where participants are invited to solve real-world problems in their environment. The implementation of the Kurikulum Merdeka (Independent Curriculum) offers a great opportunity to utilize the Project for Strengthening Pancasila Student Profiles (P5) as a platform to encourage student involvement in environmental issues. One tangible form of P5 implementation is through a project converting plastic waste into oil. The activity was conducted at SMA Negeri 5 Kota Lhokseumawe, employing the creative education method for plastic waste processing, including education and training for teachers and students, as well as project assignments for processing plastic waste through the pyrolysis process. The results of the community service activity showed that more than 80% of respondents rated the educational activities, such as material delivery, awareness-raising, and providing new insights on plastic waste processing, as excellent. Moreover, 95% expressed satisfaction with the implementation of the plastic waste processing project via the pyrolysis process, which successfully provided educational, technical, and motivational experiences to participants. Education and the plastic waste processing project have proven to offer practical solutions that not only enhance students' knowledge and skills but also drive behavioral and attitudinal changes toward the environment.